EVALUASI PELAKSANAAN PERATURAN DAERAH NOMOR 4 TAHUN 2016 TENTANG RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH KABUPATEN PONOROGO TAHUN 2016-2021 DI DESA DAYAKAN KECAMATAN BADEGAN KABUPATEN PONOROGO TAHUN 2019 (Studi Kasus Pelaksanaan Program Bantuan Pangan Non Tunai) - Rosyid Ridlo, Moh. Gufron (JI@P, 2021)
The results showed an evaluation of the implementation of Non-Cash Food Assistance (BPNT) using William Dunn with six variables, namely effectiveness, efficiency, adequacy, leveling, responsiveness and accuracy, namely: BPNT implementation starts from the stages of registration or account opening, education and socialization. , distribution, and purchase of goods at e-warong and Bank BNI 46. Achievement of BPNT implementation results, seen from BPNT objectives, is still not optimal for all BPNT KPM. The assessment of the implementation of BPNT in Dayakan Village, Badegan District, Ponorogo Regency based on William Dunn's theory is the effectiveness of achieving BPNT goals, efficiency of distribution time and the number of e-warongs or BNI 46 agents who facilitate the purchase of goods, criteria for the leveling of BPNT program recipients, and responsiveness criteria for problem handling not good. Meanwhile, the criteria for the adequacy of the results / benefits of BPNT that are felt by the poor to meet food needs and the criteria for BPNT's accuracy in answering the problems of poverty and hunger faced by the poor are quite good.